2005
DOI: 10.1152/japplphysiol.00475.2004
|View full text |Cite
|
Sign up to set email alerts
|

Role of arterial hypoxemia and pulmonary mechanics in exercise limitation in adults with cystic fibrosis

Abstract: We tested the hypothesis that maximal exercise performance in adults with cystic fibrosis is limited by arterial hypoxemia. In study 1, patients completed two maximal exercise tests, a control and a test with 400 ml of added dead space. Maximal O2 consumption was significantly lower in the added dead space study vs. control (1.04 +/- 0.15 vs. 1.20 +/- 0.11 l/min; P < 0.05), with no difference in peak ventilation. There was significant O2 desaturation during exercise that was equal in both control and added dea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 38 publications
(68 reference statements)
1
21
0
1
Order By: Relevance
“…Other factors are higher RR with lower tidal volume, hypoxemia, and poor ventilation. (20)(21)(22) In a study involving 188 healthy children between 6 and 12 years of age, the mean 6MWD was shorter than that achieved by our control group for the first 6MWT (579.4 ± 68.1 m vs. 610.3 ± 53.4 m) and the second 6MWT (569.2 ± 83.4 m vs. 616.2 ± 58.0 m). (8) However, our study included adolescents and young adults, with different anthropometric characteristics.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Other factors are higher RR with lower tidal volume, hypoxemia, and poor ventilation. (20)(21)(22) In a study involving 188 healthy children between 6 and 12 years of age, the mean 6MWD was shorter than that achieved by our control group for the first 6MWT (579.4 ± 68.1 m vs. 610.3 ± 53.4 m) and the second 6MWT (569.2 ± 83.4 m vs. 616.2 ± 58.0 m). (8) However, our study included adolescents and young adults, with different anthropometric characteristics.…”
Section: Discussionmentioning
confidence: 53%
“…More vigorous exercise and severe forms of COPD can cause major reductions in SpO 2 and reduced exercise tolerance. (22,24) The self-reported sensation of dyspnea was greater in the control group than in the CF group. Healthy children might not have the ability to measure dyspnea, because this condition is unknown in their experience.…”
Section: Discussionmentioning
confidence: 90%
“…We concluded that ventilatory limitation may be a predisposing factor for developing oxygen desaturation at peak exercise. McKone et al 13 showed that adding dead-space volume and supplemental oxygen can increase peak exercise ventilation and improve maximal exercise capacity in adult CF patients. It is unclear whether or not oxygen supplementation can be advised as a therapeutic measure in training and rehabilitation protocols for children with CF and ventilatory limitation on CPET.…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxemia results from a combination of factors such as intrapulmonary shunting, ventilation-perfusion mismatch, elevated venous admixture, and alveolar hypoventilation. 13 The primary objective of this study was to evaluate whether or not children with CF and ventilatory limitation associated with static hyperinflation are more likely to have decreased exercise capacity than CF patients without ventilatory limitation. We also evaluated whether ventilatory limitation is a predisposing risk factor for development of arterial hypoxemia during incremental exercise.…”
Section: Introductionmentioning
confidence: 99%
“…Simpler and cheaper tests such as the 6MWT have been used to assess tolerance to exercise in adult patients with CF, and the distance achieved in the walking test allows an estimation of individual response to incremental maximal exercise. Several conditions have been linked to the limited exercise capacity in adults with CF, including the deterioration of pulmonary function, peripheral muscle weakness, and malnutrition 31 . Moreover, the role of body balance as one of the main domains of functional capacity is recognized.…”
Section: Variablesmentioning
confidence: 99%